Silk fibroin and silk-based biomaterial derivatives for ideal wound dressings - Patil, Priyanka P.; Reagan, Michaela R.; Bohara, Raghvendra A. (International journal of biological macromolecules, 2020)
Silk fibroin (SF) is derived from Bombyx mori silkworm cocoons and has been used in textiles and as a suture material for decades. More recently, SF has been used for various new biomedical applications, including as a wound dressing, owing to its excellent biological and mechanical properties. Specifically, the mechanical stiffness, versatility, biocompatibility, biodegradability, water vapour permeability and slight bactericidal properties make SF an excellent candidate biomaterial for wound dressing applications. The effectiveness of SF as a wound dressing has been tested and well-documented in vitro as well as in-vivo, as described here. Dressings based on SF are currently used for treating a wide variety of chronic and acute (e.g. burn) wounds. SF and its derivatives prepared as biomaterials are available as sponges, hydrogels, nanofibrous matrices, scaffolds, micro/nanoparticles, and films. The present review discusses the potential role of SF in wound dressing and its modulation for wound dressing applications. The comparison of SF based dressings with other natural polymers understands the readers, the scope and limitation of the subject in-depth.